Guide for Fire and Explosion Investigations (The National Fire Protection Association., 2024)
NFPA 921, Guide for Fire and Explosion Investigations, provides the roadmap for scientific investigation methods used to formulate fact-based opinions on incident origin, cause, responsibility, prevention, and the damage and injuries that can arise in such cases. NFPA 921 is recommended as the forensic science consensus guide for fire investigations by the Organization of Scientific Area Committees (OSAC), a collaborative body of more than 600 forensic science practitioners and experts. Reference NFPA 921 for guidance in: Using the scientific method in origin and cause investigations Documenting an investigation so that all relevant facts are gathered for future use in court Handling fire-related evidence so that it’s admissible in court Understanding many of the terms related to explosion and fire investigations The 2024 edition includes: Additional guidance on an investigator’s potential confirmation bias, opinions, and expressions of certainty The impact of suppression activities on fire ventilation and flow path remote from the area of origin Relocation of all fire effects on electrical systems and components to Chapter 6 Four general classifications of fire causes added for investigators and authorities having jurisdiction (AHJs) Additional guidance on fire investigator safety, health, and wellness. Expanded text on investigating fire involving hybrid electric vehicles (HEVs) and electric vehicles (EVs) Revised chapter on wildfire investigations, including new terminology and unique indicators associated with these investigations.
Keywords: Badania pożarnicze; Przyczyny pożaru; przyczyny wybuchu; Dochodzenie popożarowe